2015
DOI: 10.1038/nn.4022
|View full text |Cite
|
Sign up to set email alerts
|

Social signals of safety and risk confer utility and have asymmetric effects on observers' choices

Abstract: Individuals’ risk attitudes are known to guide choices about uncertain options. However, in the presence of others’ decisions, these choices can be swayed and manifest as riskier or safer behavior than one would express alone. To test the mechanisms underlying effective social ‘nudges’ in human decision-making, we used functional neuroimaging and a task in which participants made choices about gambles alone and after observing others’ selections. Against three alternative explanations, we found that observing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(144 citation statements)
references
References 47 publications
(77 reference statements)
12
127
3
Order By: Relevance
“…S5B and the legend for details). Moreover, we found that, consistent with a previous study (16), mPFC and other regions tracked the utility signal incorporating the change in risk-preference across trials, but the neural effects were not associated with the behavioral shift across sessions (P > 0.05 for all of the activated clusters; Fig. S5C).…”
Section: Neural Encoding Of Risk Associated With the Behavioral Shiftsupporting
confidence: 89%
See 2 more Smart Citations
“…S5B and the legend for details). Moreover, we found that, consistent with a previous study (16), mPFC and other regions tracked the utility signal incorporating the change in risk-preference across trials, but the neural effects were not associated with the behavioral shift across sessions (P > 0.05 for all of the activated clusters; Fig. S5C).…”
Section: Neural Encoding Of Risk Associated With the Behavioral Shiftsupporting
confidence: 89%
“…The analysis revealed that the first model provided the better fit, indicating that the behavioral shift was better explained by a change in riskpreference. Similar analyses also revealed that it is unlikely that participants simply biased utility (16) or choice probability (24) of gambling options, possibly by copying the observee's tendency to take a gamble, without changing their own risk-preference (SI Text 3 and SI Text 4). These behavioral results together suggest that decision-making under risk can be altered by observing others' decisions through the change of one's own risk-preference.…”
Section: Significancementioning
confidence: 87%
See 1 more Smart Citation
“…A recent paper by Chung et al also found increased activity in the dACC when the choices of other group members were incongruent with the participant's own choice (Chung et al, 2015): this would be analogous to competing influences by the reward-based and socially-based components in our model. Here, we augment our understanding of the dACC's role in processing conflict by adding a third conflicting component: the participant's own choice history.…”
Section: Discussionsupporting
confidence: 55%
“…7) was selected: the vmPFC. This region was not revealed by our source conflict analysis, but has been implicated by previous studies to be involved in the prediction of outcomes based upon integration of multiple sources of information Boorman et al, 2013;Chung et al, 2015). Repeated measures ANOVA examined the relationship between activity in the vmPFC and the number of disagreeing sources according to the model above: the results of this analysis are shown in Supplementary Fig.…”
Section: Additional Neuroimaging Analysismentioning
confidence: 84%